Exploring the Communication Process between Architecture and Interior Design Departments within South African Architectural and Design Firms - Wagner, Abigail Renata (The IIE, 2021)
This study proposed to investigate the current relationship and communication of expectations between architecture and interior design departments within South African architectural and design firms. More specifically, how communication between the two influence the design development phase as well as the success of design outcomes. One of the leading obstructions to organizational efficiency is the absence of effective communication (Lunenburg, 2010). This poses a direct threat to the success of shared projects conducted by interior design and architecture departments within architectural and design businesses. Additionally, the territorial nature of the relationship between the aforementioned disciplines creates division in the work environment that negatively affects the design process (One Space, [s.a.]). The study also alludes to a lack of education regarding the uniqueness of each discipline’s role or scope of work, which in turn shapes how the respective professions communicate and work with one another (Dawkins, 2014). As a result, the core competencies of each discipline, the importance of communication during the design development phase and architects’ perception or interior design was investigated. This exploratory study hopes to inspire other researchers to further explore this topic so that a holistic conclusion could be drawn regarding the true factors that cause a disconnect between the two disciplines and how it could be overcome. This study could also contribute to academia in the form of new available literature for educational purposes in tertiary institutions, specifically those where both architectural and interior design degrees are taught. The hope is that, subsequently, the two disciplines can fully understand one another without any misperceptions of where their responsibilities and professional scopes begin or end. Alternatively, the professional contribution would therefore be to educate industry professionals to inspire a new culture of how architects and designers can collaborate, co-exist and complement one another.
Keywords: Optimal design; Perceived value; Design development; Collaboration; Effective communication